2015
DOI: 10.1155/2015/972481
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing Reveals Fungal Communities in the Rhizosphere of Xinjiang Jujube

Abstract: Fungi are important soil components as both decomposers and plant symbionts and play a major role in ecological and biogeochemical processes. However, little is known about the richness and structure of fungal communities. DNA sequencing technologies allow for the direct estimation of microbial community diversity, avoiding culture-based biases. We therefore used 454 pyrosequencing to investigate the fungal communities in the rhizosphere of Xinjiang jujube. We obtained no less than 40,488 internal transcribed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Previous studies have indicated the dominance of Ascomycota in truffle grounds (Mello et al, 2011) and in the rhizosphere of Xinjiang Jujube (Liu et al, 2015). Zygomycota was the second dominant phylum, which has also been reported as sub-dominant species in the Negev desert (Bates et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have indicated the dominance of Ascomycota in truffle grounds (Mello et al, 2011) and in the rhizosphere of Xinjiang Jujube (Liu et al, 2015). Zygomycota was the second dominant phylum, which has also been reported as sub-dominant species in the Negev desert (Bates et al, 2010).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the sequencing capability was sufficiently large to capture the complete diversity of these communities. The Chao and ACE values are indicators of species richness, and Shannon and Simpson indices are indicators of species diversity (Liu et al 2015). The bacterial community richness and diversity indices were calculated (Table 4); no significant differences observed between the two soil samples.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of unidentified sequences signify their absence in cluster analysis databases, hence the need for research to identify more environmental fungal populations and collection of curated sequences for fungal identification (Liu et al 2015). The use of RHRW with human pathogenic isolates for domestic use and irrigation purposes without any prior treatment could therefore be a cause of concern if pathogens persist up to the point of consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being an expensive technique, the 454 pyrosequencing technique is rapid and flexible with 99% accuracy (Liu et al 2015). Therefore, this study aims to assess the microbiological quality of RHRW for irrigation and domestic purposes using culturable and non-culturable approaches for bacteria and fungi, respectively.…”
Section: Stated Thatmentioning
confidence: 99%